Waste biomass-based 3D graphene aerogels for high performance zinc-ion hybrid supercapacitors - Sankar Das G.; Jangir L.K.; Raju K.S.; Sharma Y.C.; Tripathi K.M. (My University, 2025)
Biomass-based 3D graphene aerogels were explored as cathode materials for the fabrication of high-performance zinc-ion hybrid supercapacitors. These hybrid supercapacitors delivered a high specific capacitance of ∼353.1 F g−1 at a current density of 0.1 A g−1 and maximum specific energy and power of 158.9 W h kg−1 (at 84 W kg−1 of specific power) and 14.8 kW kg−1 (at 77.2 W h kg−1 of specific energy), respectively. These devices exhibited a remarkable rate capability at high current densities and excellent capacity retention, retaining ∼84.2% of their capacity with ∼100% coulombic efficiency up to 10 000 cycles at 10 A g−1 © 2024 The Royal Society of Chemistry.